Association between income and control of cardiovascular risk factors after acute coronary syndromes: an observational study (Swiss Medical Weekly, 2019)
BACKGROUND The role of income in cardiovascular disease prevention after an acute coronary syndrome (ACS) remains unclear. We aimed to assess the association between income and control of cardiovascular risk factors one year after an ACS in a country with universal health insurance. METHODS Between 2013 and 2014, we studied 255 consecutive patients with ACS in an observational study in a university hospital in Switzerland in which self-reported household income was assessed. We classified patients into two categories based on the median income in Switzerland: higher than CHF 6000 (€ 5300) or less than or equal to CHF 6000 (€ 5300) per month. One year after discharge, patients were evaluated for the achievement of lipid and blood pressure targets, smoking cessation and drug adherence. Multivariate odds ratios (OR) were adjusted for age, sex, education, living status and working status. RESULTS Overall, 52.2% (n = 133) of patients with ACS were in the low-income category and 47.8% (n = 122) were in the high-income category. One year after discharge, high-income patients had higher rates of smoking cessation (64.2 vs 30.1%, multivariate-adjusted odds ratio (OR) 3.82, 95% confidence interval (CI) 1.58–9.24) and blood pressure target achievement (78.6 vs 60.2%, multivariate-adjusted OR 2.19, 95% CI 1.09–4.41) compared to those in the low-income category. There were no differences regarding adherence to drugs or lipid control between the two income groups. CONCLUSION A high household income was associated with a higher rate of smoking cessation and better control of blood pressure one year after ACS, independently of education, living status and working status.